Enhancing Job Satisfaction through Organizational Support and Authentic Leadership in Machinery and Heavy Equipment Manufacturing: Work Engagement as a Mediator - Nindya Putri Rachmandani; Dita Oki Berliyanti; B Medina Nilasari (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the effects of perceived organizational support and authentic leadership on job satisfaction among employees in the machinery and heavy equipment manufacturing industry, with work engagement serving as a mediating variable.Method: This quantitative study involved 238 employees from machinery and heavy equipment manufacturing companies in the Greater Jakarta area, Indonesia. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: The findings demonstrate that perceived organizational support has positive effects on both job satisfaction and work engagement. Authentic leadership has a positive direct effect on work engagement but does not directly affect job satisfaction. Furthermore, work engagement mediates the effects of both perceived organizational support and authentic leadership on job satisfaction.Practical Implications for Economic Growth and Development: Companies should strengthen organizational support, foster authentic leadership practices, and promote employee work engagement to improve job satisfaction. These initiatives may contribute to stronger organizational performance, improved productivity, and the achievement of organizational goals.Originality/Value: Unlike previous studies that have generally examined perceived organizational support and authentic leadership separately, this study integrates both variables into a single mediation model involving work engagement to explain job satisfaction. The findings reveal that authentic leadership influences job satisfaction only indirectly through work engagement.